EFEKTIVITAS PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP PENINGKATAN KESEJAHTERAAN PETANI DI DESA SALO DUA KECAMATAN MAIWA KABUPATEN ENREKANG - Syarifuddin, Renny; Adnan, Andi Astina; Uceng, A (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the Effectiveness of Village-Owned Enterprise Management (BUMDes) towards Improving the Welfare of Farmers. The population in this study was 35 members of Village-Owned Enterprises (BUMDes) from January to March in Salo Dua Village, Maiwa District, Enrekang Regency. The sampling technique uses a saturated sample where the entire population is sampled. This type of research is quantitative descriptive. The data collection techniques used in this research are, observation, literature study and questionnaire. The data analysis technique used is a validity test, reliability, using the help of the IBM SPSS statistic 26.0 Application. The results of this study found that the Effectiveness of Village Owned Enterprise Management (BUMDes) from the results of the questionnaire was obtained by a variable recapitulation. The effectiveness of 60% is in the "less good" category, and the 54% increase in the "not good" category variable recapitulation is in the "not good". The factors that affect the effectiveness of Village Owned Enterprise Management (BUMDes) are the apparatus quality factor of 59%, the administrator competition factor of 60% and the supervision factor of 66%. In addition, the influence between the Effectiveness of Village Owned Enterprise Management (BUMDes) and the Improvement of Farmer Welfare in Salo Dua Village is categorized as "influential/significant". From the ANOVA Fhitung test obtained by 21,202 with a significant level of 0.000, this shows that the influence of independent variables has a significant effect, and the probability is far above 0.05, partially the calculated value of t (4,605) ≥ t table (1.692) means that the effectiveness of Village-Owned Enterprise Management (BUMDes) has an effect/significantly on the Improvement of Farmer Welfare in Salo Dua Village, Maiwa District, Enrekang Regency.